Conservation units, the influence of economic power on the territory (Research, Society and Development, 2021)
The development model based on the deliberate extraction of natural resources resulted in the degradation of the environment, with that, measures were taken, such as the creation of Conservation Units - UC in order to protect nature for current and future generations. However, there are two types of UCs, Sustainable Use and Integral Protection, which allow the extraction of natural resources and the other only allows the use of indirect resources, respectively. This work aims to demonstrate how economic power has influenced these UCs, since, close to the main driving forces of the State, there are more UCs that allow the direct use of resources, that is, direct appropriation of natural resources for income generation. For the approach given through the map, it was shown that the territory is organized according to the economic power in relation to the Conservation Units in the State of Pará.